PERSIAPAN SDM UNGGUL MEMALUI PEMBELAJARAN RASA, KARSA, CIPTA DAN KARYA DALAM PENDIDIKAN ERA REVOLUSI 4.0 DI SMK NEGERI 8 PALEMBANG - Hendri Gunawan; Diana Widhi Rachmawati; Neta Dian Lestari; Masnunah; Erma Yulaini; Nova Pratiwi; Chandra Kurniawan; Januardi; Boby Agus Yusmiono (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The methods used in Community Service activities are: lectures, questions and answers, discussions at SMK Negeri 8 Palembang. The theme raised was "Preparation of Excellent Elementary School through Learning of Sense, Intention, Creation and Work in Education in the Revolutionary Era 4.0 at Public High School 8 Palembang". The resource persons for this activity were permanent lecturers of FKIP, PGRI University Palembang. Participants of this activity were students and teachers of SMK Negeri 8 Palembang. The activities of the PkM team have been carried out well and have been completed according to the predetermined time. After each lecturer gave an explanation, they were given the opportunity to ask some questions. In conclusion, this community service report is carried out and completed through procedures in a true manner which is expected to contribute to science in students. and teachers not only that, the PkM activities which were held on Monday, November 16, 2019 can also increase and arouse the sense of professionalism of lecturers in the FKIP PGRI University of Palembang and increase the knowledge and understanding of students, especially teachers and students at SMK Negeri 8 Palembang. Suggestions, the hope is that this activity can continue to be carried out in a sustainable manner to provide knowledge and deepen the knowledge or understanding of teachers and students about preparing superior human resources by learning about taste, initiative, creativity and work in education in the revolutionary era 4.0